The role of eosinophils and their activation state in hypereosinophilia-associated heart disease - Sunusi, Usman; Osuji, Immaculeta; Ziegelmeyer, Benjamin; Medvedovic, Mario; Todd, Haley; Abou-Khalil, Joe; Zimmermann, Nives (Frontiers in Immunology, 2025)
BackgroundCardiac complications in patients with hypereosinophilia cause significant morbidity and mortality. However, mechanisms of how eosinophilic inflammation causes heart damage are poorly understood.MethodsWe developed a model of hypereosinophilia-associated heart disease by challenging hypereosinophilic mice with a peptide from the cardiac myosin heavy chain. Disease outcomes were measured by histology, immunohistochemistry, flow cytometry, and measurement of cells and biomarkers in peripheral blood. Eosinophil dependence was determined by using eosinophil-deficient mice (ΔdblGATA). Single cells from the heart were subjected to single-cell RNA sequencing to assess cell composition, activation states, and expression profiles. In vitro studies used bone marrow-derived eosinophils (BMDeos) and stimulated them with cytokines and pathogen-associated molecular patterns, followed by assessment of activation markers by flow cytometry.ResultsMice challenged with the myocarditic and control peptide had peripheral blood leukocytosis, but only those challenged with the myocarditic peptide had heart inflammation. Heart tissue was infiltrated by eosinophil-rich inflammatory infiltrates associated with cardiomyocyte damage. Disease penetrance and severity were decreased in eosinophil-deficient mice. Single-cell RNA sequencing showed the enrichment of myeloid cells, T cells, and granulocytes (neutrophils and eosinophils) in myocarditic mice. Focusing on eosinophils, there was increased expression of genes associated with type 1 cell activation (such as CD274/PDL1), complement activation, and pathogen-associated molecular pattern recognition. To verify findings generated by single-cell RNA sequencing on a protein level, we performed flow cytometry analysis and assessed the level of type 1 and type 2 biomarkers CD274 and CD101, respectively. The proportion of cells expressing surface CD274 increased on both neutrophils and eosinophils, particularly in mice that showed inflammation by histology. There was no significant increase in expression of CD101. Finally, we assessed whether activation markers can be induced on eosinophils in vitro. Interferon γ (IFNγ) markedly increased expression of CD274, consistent with type 1 polarization. Furthermore, BMDeos stimulated with LPS showed a concentration-dependent increase in the level of CD274 expression.ConclusionEosinophils are required for heart damage in hypereosinophilia-associated heart disease. Heart-infiltrating eosinophils in an inflammatory condition show type 1 activation, which can be recapitulated in vitro.